Proliferative effect of the aqueous extract of Hyptis pectinata on liver regeneration after partial hepatectomy in rats - Melo,Gustavo Barreto (2006)
PURPOSE: This study was carried out to assess the effects of the aqueous extract of Hyptis pectinata leaves on liver regeneration and on serum enzymes (AST, ALT and gamma-GT) after 67% partial hepatectomy in rats. METHODS: AST, ALT and gamma-GT, were determined by conventional procedures using a spectrophotometer (Model E2250-CELM). Liver regeneration was evaluated by immunohistochemical staining for proliferating cell nuclear antigen (PCNA). RESULTS:Oral pretreatment during 4 days at 100 mg/kg increased liver regeneration index. At 200 mg/kg, AST level was statistically decreased in comparison to the group submited to distilled water administration. The other enzymes assessed disclosed no difference when all groups were compared. CONCLUSION: The present study shows that the aqueous extract of Hyptis pectinata leaves contains some biological active principles that stimulate liver regeneration at 100 mg/kg and cause slight hepatic protection at 200 mg/kg.